Comparative Effects of High Hydrostatic Pressure and Thermal Processing on Physicochemical Properties and Bioactive Components of Mao Luang (Antidesma bunius Linn.) Juice - Pittaya Chaikham (Science Faculty of Chiang Mai University, 2019)
Mao Luang juices were pressurized at 100 - 500 MPa at 25°C for 5 - 15 min and pasteurized at 90°C for 1 min, before their polyphenol oxidase activity, ascorbic acid, total anthocyanins, total phenols, antioxidant capacity (DPPH and FRAP assays) and color parameters were determined. It was found that polyphenol oxidase was completely inactivated in pasteurized juice, while in pressurized juices at 100, 300 and 500 MPa, the activities were 110 - 126%, 112 - 131% and 81 - 90%, respectively. The levels of ascorbic acid, total anthocyanins, total phenols and antioxidant capacity in pressurized Mao Luang juices were significantly higher than in thermally treated sample. For color parameter, the retention of redness (a*) of pressurized batches was greater than the others. This indicates high pressure processing could be an alternative technique to preserve the qualities of Mao Luang juice.